2023
DOI: 10.3390/ma16031001
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Tribological Behaviour of Various AMC Surfaces against Brake Lining Material

Abstract: AlSi7Mg/SiCp aluminium matrix composites (AMCs) with a high ceramic content (35 vol.%) that were produced by using the field-assisted sintering technique (FAST) were subjected to tribological preconditioning and evaluated as a potential lightweight material to substitute grey cast iron brake discs. However, since an uncontrolled running-in process of the AMC surface can lead to severe wear and thus to failure of the friction system, AMC surfaces cannot be used directly after finishing and have to be preconditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(13 citation statements)
references
References 18 publications
(39 reference statements)
1
12
0
Order By: Relevance
“…Former investigations by the authors of this paper on AMC friction surfaces showed that the kinematic roughness generated by face turning influences the formation behaviour of the tribosurface [12,13]. The results showed that specimen surfaces with higher values for the roughness led more quickly to a homogeneously closed tribosurface.…”
Section: Introductionmentioning
confidence: 67%
See 3 more Smart Citations
“…Former investigations by the authors of this paper on AMC friction surfaces showed that the kinematic roughness generated by face turning influences the formation behaviour of the tribosurface [12,13]. The results showed that specimen surfaces with higher values for the roughness led more quickly to a homogeneously closed tribosurface.…”
Section: Introductionmentioning
confidence: 67%
“…The machined AMC specimens were prepared for the tribological test according to previous investigations [12,13]. The AMC specimens were fixed in a pin-on-disc test bench (SRV, Optimol Instruments Prüftechnik GmbH, Munich, Germany).…”
Section: Tribological Surface Conditioning Using Pin-on-disc Testmentioning
confidence: 99%
See 2 more Smart Citations
“…This trend already exists especially due to the beginning commercialisation of AMC brake discs, although mass production processes are currently lacking. Despite the nearly wear-free behaviour of highparticle-reinforced AMC in tribological contact with semi-metallic brake lining material [2], a significant amount of AMC scrap with a high content of ceramic hard phases is to be expected at the end of the latest car life cycle.…”
Section: Introductionmentioning
confidence: 99%